2011
DOI: 10.1111/j.1365-2052.2011.02211.x
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in the imprinted bovine insulin‐like growth factor 2 receptor gene (IGF2R) are associated with body size traits in Irish Holstein‐Friesian cattle

Abstract: The regulation of the bioavailability of insulin-like growth factors (IGFs) is critical for normal mammalian growth and development. The imprinted insulin-like growth factor 2 receptor gene (IGF2R) encodes a transmembrane protein receptor that acts to sequester and degrade excess circulating insulin-like growth factor 2 (IGF-II) - a potent foetal mitogen - and is considered an important inhibitor of growth. Consequently, IGF2R may serve as a candidate gene underlying important growth- and body-related quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…This included analysis of genotypes previously reported by this group in IGF1 [4], IGF2R, IGF2 [31,32], GH1 [5] and GHR [7]. …”
Section: Methodsmentioning
confidence: 99%
“…This included analysis of genotypes previously reported by this group in IGF1 [4], IGF2R, IGF2 [31,32], GH1 [5] and GHR [7]. …”
Section: Methodsmentioning
confidence: 99%
“…Differential expression of IGF2 already was known to be prevalent in the pathogenesis of the developmental disease BWS (Waterland et al 2006), and this study revealed epigenetic changes at the gene locus as a causative factor. As discussed earlier, this gene has been associated with several important traits in cattle, such as oocyte competency and milk yield (Flisikowski et al 2007;Fagundes et al 2011;Berkowicz et al 2012). Epigenetic changes in this gene could therefore have important implications for regulation of fertility and production traits in cattle.…”
Section: Epigenetics and Nutritionmentioning
confidence: 93%
“…Loss of imprinting at this gene has been associated with growth disorders in humans as well as the onset of diseases such as cancer (Chao & D'Amore 2008). Relevantly, both this gene and its receptor (IGF2R) also have been shown to influence several complex performance traits in cattle, including body size and carcass traits (Imumorin et al 2011;Magee et al 2011;Berkowicz et al 2012;Sikora et al 2012). However, genetic improvement schemes in livestock assume that the expression of desirable traits is independent of parental origin (de Vries et al 1994).…”
Section: Epigenetics and Inheritancementioning
confidence: 99%
See 1 more Smart Citation
“…FFRC strain common carp IGF2R intron one polymorphisms and effect of sex on body weight Berkowicz et al (2011) quantified genotype-phenotype associations between 3 intronic bovine IGF2R SNPs and body size traits in Irish Holstein-Friesian sires. Kaku et al (2007) also observed a significant difference in birth weight among the 3 neonatal c.901C>G genotypes of the IGF2R gene (i.e., CC, CG, and GG).…”
Section: Ffrc Strain Common Carp Igf2r Intron One Polymorphismsmentioning
confidence: 99%